1998
DOI: 10.1029/98jb01351
|View full text |Cite
|
Sign up to set email alerts
|

Stability limits of hydrous minerals in sediment and mid‐ocean ridge basalt compositions: Implications for water transport in subduction zones

Abstract: Abstract. Phase relationships in hydrated natural sediment and mid-ocean ridge basalt (MORB) compositions were investigated experimentally from 6 to 15 GPa and 700øC to 1400øC in order to determine the stability of hydrous phases in subducting slabs and to constrain reactions resulting in the release of water from subduction zones to the mantle. Phengite and hydrous aluminum silicates (topaz-OH and phase egg) are stable in the sediment composition at depths greater than 150 km and constitute H20 reservoirs. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
165
4
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(178 citation statements)
references
References 45 publications
7
165
4
2
Order By: Relevance
“…The mineral proportion changes in the MORB composition as a function of pressure at subducting slab temperatures (800-1200°C) have been investigated by previous studies (e.g., Irifune et al, 1986;Ono, 1998;Maruyama, 1999, 2004;Aoki and Takahashi, 2004). These studies reported that the M cpx is~0.5-0.7 at about 4 GPa.…”
Section: Connectivity Of Hydrous Liquid In the Eclogite Systemmentioning
confidence: 97%
“…The mineral proportion changes in the MORB composition as a function of pressure at subducting slab temperatures (800-1200°C) have been investigated by previous studies (e.g., Irifune et al, 1986;Ono, 1998;Maruyama, 1999, 2004;Aoki and Takahashi, 2004). These studies reported that the M cpx is~0.5-0.7 at about 4 GPa.…”
Section: Connectivity Of Hydrous Liquid In the Eclogite Systemmentioning
confidence: 97%
“…Beyond ca. 9 GPa, after dehydration of lawsonite and phengite (Schmidt and Poli 1998;Ono 1998), only few hydrous phases remain stable, for example, topaz-OH and phase egg in peraluminous sediments (Ono 1998) and hydrous alphabet phases in peridotite (Komabayashi et al 2004). With depth, these hydrous phases become minor in abundance, and most of the H 2 O in the subducting slab becomes stored in nominally anhydrous phases .…”
mentioning
confidence: 99%
“…The strategy to study a carbonated water-poor or dry pelite results from the fact that after the reaction of phengite to K-hollandite near 9 GPa (Domanik and Holloway 1998;Ono 1998) hydrous minerals are limited or absent and flush melting (Poli and Schmidt 2002) of sediments assisted by fluids derived from underlying oceanic basalts or serpentinized peridotites is limited to 9 and 6-7 GPa, respectively (Kawamoto et al 1996;Schmidt and Poli 1998). Furthermore, sodium becomes compatible in clinopyroxene at C3.5 GPa , leaving potassium that strongly depresses the solidus temperature of subducted sediments.…”
mentioning
confidence: 99%
“…Various studies have been conducted to date to clarify the stability of hydrous phases in peridotitc, basalt, and sediment compositions at high pressure and temperature [e.g., Schmidt and Poll, 1998; Ono, 1998]. …”
Section: Introductionmentioning
confidence: 99%